Broadband Services Quality of Experience on Public Higher Educational Institution Users: A Research Direction - Che Sobry, Suheil; Wahab, Muhammad Zarunnaim Wahab; Muhammad, Mohd Hilal; Ismail, Muhammad Saiful Islam; Manshor, Ruzita; Mohd Saufi, Mohd Shahid Azim; Nor A’zam, Muhammad Khairul Zharif (Information Management and Business Review, 2024)
Internet access is crucial in facilitating effective learning and communication. However, disparities in internet quality persist, especially within Public Higher Educational Institutions (PHEIs). Despite efforts by broadband providers to enhance services, complaints regarding quality persist among students and staff. Thus, this research aims to investigate users’ Quality of Experience (QoE) with broadband services in PHEI campuses, focusing on coverage, service quality, reliability, and usability. Additionally, it seeks to identify user preferences and usage patterns, correlate broadband quality with user satisfaction, and propose improvements. A comprehensive methodology integrating qualitative and quantitative approaches, including surveys, and interviews is proposed. The implications of this research extend to regulatory and policy actions, including infrastructure improvement, ensuring quality of service, supporting online learning, and encouraging research and innovation in broadband technologies. This study aims to inform stakeholders and contribute to enhancing broadband access and quality in PHEIs, ultimately improving educational outcomes and experiences.